Observable carbon isotope fractionation in the photodegradation of polybrominated diphenyl ethers by simulated sunlight. (March 2021) - Ren, Zihe; Zeng, Yanhong; Luo, Xiaojun; Huang, Chenchen; Tian, Yankuan; Gao, Shutao; Mai, Bixian
Abstract: In the present study, carbon isotope effects were investigated during the photodegradation of polybrominated diphenyl ethers (PBDEs) by compound-specific stable isotope analysis (CSIA). Five PBDE congeners (BDE 85, 99, 100, 153 and 154) in n-hexane were individually exposed to simulated sunlight for as long as 15 h, except for BDE 100 (24 h). Consecutive debromination of PBDE by photolysis in n-hexane was confirmed by the clear 13 C enrichment of mother congeners and successive depletion of δ 13 C values for the photodegradation products with decreasing degree of bromination, which can be attributed to mass-dependent isotope fractionation. The observed variation in the isotope fractionation trends for the para -debrominated products might be linked to the different photocatalytic activities of the PBDE congeners. Higher fractionation was observed for penta-BDEs (εc= −2.2 ± 0.45‰ and −2.3 ± 0.26‰ for BDE 85 and BDE 99, respectively) compared to that for hexa-BDEs (εc= −1.7 ± 0.41‰, and −1.3 ± 0.12‰ for BDE 153 and BDE 154, respectively). Normal isotope effects (AKIE > 1) observed in our study supports the utility of CSIA for the evaluation of the photodegradation of PBDEs. Highlights: Carbon isotope fractionation during the photolysis of PBDEs was investigated. Alterations to δ 13 C values are further proof of the photodegradation of PBDEs. Diverse δ 13 C values of products agree with different PBDE photolysis activities. Higher fractionation was observed for penta-BDEs than for hexa-BDEs.